Eating disorders in male runners - Harris, J.; Peterson, J. T. (Strength and Conditioning Journal, 2020)
This article aims to evaluate current literature related to the prevalence and consequences of eating disorders (EDs) among male runners. Historically, research was disproportionately aimed at female runners, hindering the assessment and clinical management of EDs in male runners. This literature review provides coaches with a deeper understanding of EDs in male runners. In addition, the physiological and psychological consequences attributed to a diagnosis of an ED in male runners are discussed. Suggestions for early identification and coaching strategies are provided. Future research is encouraged to provide a deeper understanding of the prevalence and significance of EDs in male runners.